BENTUK DAN FUNGSI BAHASA JAWA DALAM INTERAKSI SOSIAL MASYARAKAT KRATON SURAKARTA HADININGRAT - Eka Susylowati (Multilingual, 2019)
The use of Javanese is an interesting phenomenon both oral and written. The Javanese language used in the Surakarta Hadiningrat palace as a communication device is still familiar with speech levels. The use language levels ranging from ngoko, madya, krama, krama inggril, or even kedhaton language. The purpose of this study is to describe the pattern of verbal interaction and social function of Javanese language in the Surakarta Hadiningrat palace community. This research is a qualitative research by taking the location of research in the Surakarta Hadiningrat Palace. The data used is Javanese in daily activities and traditional ceremonies in the palace. The data is in oral and written form. The data is provided by observation and interview methods. In data analysis using a contextual approach, the speech component. From the results of the study it is concluded that the patterns of the use of Javanese language in the palace community is influenced by the vertical and horizontal relationship between locutorand interlocutor. The function of using Javanese language in the Surakarta palace community as follows as an official communication tool in the palace, as an expression of respect, creates politeness.